MENGHAYATI AJARAN HINDU KE DALAM DIRI - Sutarti, Titin (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2019)
Atman, which acts as the existence of life and the source of life for all beings, is the source of life in the life of this universe, human, animal and plant. In the teachings of Hinduism explained that